DEVELOPMENT EXPERIENCE OF MODERN MADE IN RUSSIA BOILER INSTALLATIONS - A. N. Tugov; G. A. Ryabov; A. V. Shtegman; M. N. Maidanik (Известия высших учебных заведений: Проблемы энергетики)
Based on the results of adjustment, testing and industrial development of the main models of boiler units commissioned by Russian thermal power stations in recent years, the level of the domestic boiler plant is shown. The ways of improving these head samples are outlined. Prospective directions of development of domestic boiler plants are given, to which special attention should be paid to scientific research organizations and boiler plants.